In vitro evaluation of gene expression changes for gonadotropin‐releasing hormone 1, brain‐derived neurotrophic factor and neurotrophic tyrosine kinase, receptor, type 2, in response to bisphenol A treatment. (11th March 2013) - Warita, Katsuhiko; Mitsuhashi, Tomoko; Ohta, Ken‐ichi; Suzuki, Shingo; Hoshi, Nobuhiko; Miki, Takanori; Takeuchi, Yoshiki
Abstract We evaluated the effects of bisphenol A (BPA) on embryonic mouse hypothalamic cells. Real‐time reverse transcription polymerase chain reaction (RT‐PCR) indicated that gonadotropin‐releasing hormone 1 (Gnrh1) expression in 0.02–20 μM BPA‐treated cells did not differ from that in control cells but decreased significantly in 200 μM BPA‐treated cells. The mRNA level for brain‐derived neurotrophic factor (Bdnf), which participates in GNRH1 secretory system development, decreased significantly in 200 μM BPA‐treated cells, but that for neurotrophic tyrosine kinase, receptor, type 2 (Ntrk2), did not change. This indicates that Gnrh1 gene expression in mice fetuses is not affected by exposure to <20 μM BPA and that the adverse effects of BPA on the BDNF‐NTRK2 neurotrophin system are induced by decrease in the mRNA level of the ligand, not of its receptor.